Anverenes B–E, New Polyhalogenated Monoterpenes from the Antarctic Red Alga Plocamium cartilagineum - Andrew J. Shilling; Jacqueline L. von Salm; Anthony R. Sanchez; Younghoon Kee; Charles D. Amsler; James B. McClintock; Bill J. Baker (Marine Drugs, 2019)
The subtidal red alga Plocamium cartilagineum was collected from the Western Antarctic Peninsula during the 2011 and 2017 austral summers. Bulk collections from specific sites corresponded to chemogroups identified by Young et al. in 2013. One of the chemogroups yielded several known acyclic halogenated monoterpenes (2–5) as well as undescribed compounds of the same class, anverenes B–D (6–8). Examination of another chemogroup yielded an undescribed cyclic halogenated monoterpene anverene E (9) as its major secondary metabolite. Elucidation of structures was achieved through one-dimensional (1D) and 2D nuclear magnetic resonance (NMR) spectroscopy and negative chemical ionization mass spectrometry. Compounds 1–9 show moderate cytotoxicity against cervical cancer (HeLa) cells.